ЗАЛЕЖНІСТЬ ДИНАМІЧНИХ ХАРАКТЕРИСТИК ІМПУЛЬСНИХ СТРУМІВ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК ВІД ВІДДАЛЕНОСТІ ЇХНЬОГО ТЕХНОЛОГІЧНОГО НАВАНТАЖЕННЯ - Щерба, А.А.; Супруновська, Н.І.; Щерба, М.А.; Розискулов, С.С.; Михайленко, В.В. (Інститут електродинаміки Національної академії наук України, 2022)
The paper investigates the influence of the distant technological load from electric discharge installations (EDIs) with capacitive storage of electricity on the dynamic characteristics of impulse currents in the load. On the basis of experimental studies, the peculiarities of changing the dynamic characteristics of EDIs, such as the average rate of rise and fall of their output pulse current during the implementation of volumetric spark dispersion of a layer of metal granules in dielectric liquids between electrodes, were determined. The influence of the length of such types of connecting conductors as twisted pair, coaxial cable, and litzendraht with bifilar winding of current-carrying conductors on the output dynamic characteristics of the EDI was analyzed. A significant influence of the type of connecting conductors of considerable length on the indicated characteristics has been established, especially in the case of a low-inductance of the load circuit of the EDI. It is substantiated that when the technological load is significantly distant (several meters) from the EDI, it is quite appropriate to use power cables with solid polymer electrical insulation as connecting conductors of the coaxial type. Ref. 10, fig. 2, tables 2.